2020
DOI: 10.1111/jch.13949
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality is associated with cardiac autonomic dysfunction in treated hypertensive men

Abstract: Hypertensives present cardiac autonomic dysfunction. Reduction in sleep quality increases blood pressure (BP) and favors hypertension development. Previous studies suggested a relationship between cardiovascular autonomic dysfunction and sleep quality, but it is unclear whether this association is present in hypertensives. Thus, this study evaluated the relationship between sleep quality and cardiac autonomic modulation in hypertensives. Forty‐seven middle‐aged hypertensive men under consistent anti‐hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Similarly, as aforementioned, we were not able to identify specific cardiac mechanisms linking sleep quality to increased HRV. Future studies could consider the inclusion of baroreflex sensitivity assessment, which may alter arterial pressure and therefore modulate both sympathetic and vagal activity (Oliveira-Silva et al, 2020; Tsai et al, 2021). Future studies should evaluate the aforementioned relationships with a higher level of disaggregation by means of the structural equation modeling approach, such as a full-SEM approach or with a sum or average of a subset of items (i.e., parcels) used as indicators for a latent variable (i.e., partial disaggregated models) (see Coffman & MacCallum, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, as aforementioned, we were not able to identify specific cardiac mechanisms linking sleep quality to increased HRV. Future studies could consider the inclusion of baroreflex sensitivity assessment, which may alter arterial pressure and therefore modulate both sympathetic and vagal activity (Oliveira-Silva et al, 2020; Tsai et al, 2021). Future studies should evaluate the aforementioned relationships with a higher level of disaggregation by means of the structural equation modeling approach, such as a full-SEM approach or with a sum or average of a subset of items (i.e., parcels) used as indicators for a latent variable (i.e., partial disaggregated models) (see Coffman & MacCallum, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Also, sleep duration and quality may impact next-day cardiac vagal tone. For instance, lower resting HRV was observed after sleep deprivation (Zhong et al, 2005) and in individuals with poorer subjective sleep quality (Castro-Diehl et al, 2016; Oliveira-Silva et al, 2020). Moreover, difficulties in initiating sleep were recently associated with lower resting HRV during the next day in adults (Tsai et al, 2021) and children (Michels et al, 2013).…”
mentioning
confidence: 99%
“…An inverse association was observed between a healthy sleep score and DM outcome among hypertensives (HR = 0.78; 95% CI 0.75–0.81), similar to our results (HR = 0.89; 95% CI 0.87–0.92). A few researchers pointed out that poor sleep quality assessed by specific sleep patterns was related to several risk factors of CVD among hypertensives [ 36 , 37 ]. Additionally, the relationship between a single dimension of sleep and the prognosis of hypertension, such as CVD complications, has been assessed previously [ 20 , 21 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Poor quality of sleep has been associated with blood pressure in children and adolescents from Brazil [ 31 ] and the United States [ 28 ]. Poor quality of sleep has been reported to increase BP through increased sympathetic activity and/or reduced parasympathetic activity, which may lead to a sympathovagal imbalance in patients with hypertension [ 32 ], myocardial infarction [ 14 ], and in children at risk to obesity [ 13 ]. The association between poor quality of sleep and anthropometric indices has been reported to be inconsistent in meta-analysis with some studies favouring a positive association, while other studies, especially in college students, reported no association [ 33 ].…”
Section: Discussionmentioning
confidence: 99%